2021
DOI: 10.3390/atmos12121703
|View full text |Cite
|
Sign up to set email alerts
|

Four- and Five-Carbon Dicarboxylic Acids Present in Secondary Organic Aerosol Produced from Anthropogenic and Biogenic Volatile Organic Compounds

Abstract: To better understand precursors of dicarboxylic acids in ambient secondary organic aerosol (SOA), we studied C4–C9 dicarboxylic acids present in SOA formed from the oxidation of toluene, naphthalene, α-pinene, and isoprene. C4–C9 dicarboxylic acids present in SOA were analyzed by offline derivatization gas chromatography–mass spectrometry. We revealed that C4 dicarboxylic acids including succinic acid, maleic acid, fumaric acid, malic acid, DL-tartaric acid, and meso-tartaric acid are produced by the photooxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…As can be seen in Table 1, five main acids, succinic acid, benzoic acid, phthalic acid, glutaric acid, and adipic acid, were identified and quantified. Succinic acid was observed almost in every sample and its higher prevalence could possibly be explained by the fact that it can be formed from common biogenic and anthropogenic precursors such as isoprene and toluene (Sato et al, 2021). The aromatic acids such as benzoic acid and phthalic acid were also detected in the samples.…”
Section: 5analysis Of Aerosol Particles Collected By Itex With Ptfe F...mentioning
confidence: 95%
“…As can be seen in Table 1, five main acids, succinic acid, benzoic acid, phthalic acid, glutaric acid, and adipic acid, were identified and quantified. Succinic acid was observed almost in every sample and its higher prevalence could possibly be explained by the fact that it can be formed from common biogenic and anthropogenic precursors such as isoprene and toluene (Sato et al, 2021). The aromatic acids such as benzoic acid and phthalic acid were also detected in the samples.…”
Section: 5analysis Of Aerosol Particles Collected By Itex With Ptfe F...mentioning
confidence: 95%
“…5,12,26,27,30,44 Malic acid has been proposed to be a higher-generation oxidation product of terpenes based on a high correlation with terpene markers in field studies and in chamber experiments. 12,45 However, it is not a very specific marker as it can be formed from other precursors from anthropogenic and biogenic sources. 45…”
Section: Oxidized Compounds In the Atmospherementioning
confidence: 99%
“…12,45 However, it is not a very specific marker as it can be formed from other precursors from anthropogenic and biogenic sources. 45…”
Section: Oxidized Compounds In the Atmospherementioning
confidence: 99%
“…In general, the Amazon basin is an important source of aerosols dominated mainly by organic matter in both fine and coarse fractions. Biomass burning and haphazard land use also interfere with the natural cycle of the region. The high solubility of MA also facilitates the formation of aerosol particles in humid climatic conditions. , A study on the glyoxal uptake of aerosol made from MA demonstrated the importance of acidic conditions in formation of organic aerosols …”
Section: Introductionmentioning
confidence: 99%
“…The high solubility of MA also facilitates the formation of aerosol particles in humid climatic conditions. 65,66 A study on the glyoxal uptake of aerosol made from MA demonstrated the importance of acidic conditions in formation of organic aerosols. 67 In the present work, we investigate the hydrogen-bonded complexes of MA with several naturally occurring organic amines such as methylamine (MMA, CH 3 NH 2 ), dimethylamine [DMA, (CH 3 ) 2 NH], trimethylamine [TMA, (CH 3 ) 3 N], and ammonia (NH 3 ) to analyze some of their quantumchemical properties that might be relevant in the context of the atmospheric nucleation process.…”
Section: Introductionmentioning
confidence: 99%